Plant population with irrigated wheat - Coqueiro, Erycson Pires; Andrade, José Maria Vilela de (Pesquisa Agropecuaria Brasileira, 2014)
Five field experiments were carried out from 1966 to 1970, in Sete Lagoas, Minas Gerais, to determine the effect of seeding rates on grain yield of irrigated wheat. By using the averages of the five experiments in regression equations it was shown that optimal spacing was 21 cm between rows and optimal population density was 256 seeds per square meter. The confidence intervals calculated at the 5% probability level were: spacing, 16 to 26 cm and density 131 to 330 seeds/m2.